Penguatan Moral Melalui Pendidikan Agama Terinteragrasi Desa Sembungjambu Kecamatan Bojong Kabupaten Pekalongan - Mochammad Najmul Afad; Aris Priyanto; Abdul Basid; Nur Fajariyah; Milda Irbayani (Turast: Jurnal Penelitian dan Pengabdian, 2023)
Sembungjambu Village has local potential and needs to develop including community traditions that are still being carried out and there are two tombs of the guardian Mbah Kyai Gede Ceper and Mbah Datuk. Nevertheless, Sembungjambu Village has social problems, one of which is a moral decline marked by promiscuity, alcoholism, and a community that is considered deviant or deviates from the norms of the local community. One effort to overcome moral degradation is through religious education. This community empowerment activity uses the Participatory Rural Appraisal (PRA) method, a participatory empowerment model implemented in the village. This activity was carried out in three stages, namely first planning, second, implementation, and third evaluation. These empowerment activities include organizing community leaders from Sembungjambu Village from all elements who have concerns over the issue of moral decline, mapping community potential that can be used for the Moral Strengthening process through Focus Group Discussions, Mapping formal, non-formal and informal educational institutions in Sembungjambu Village which will later produce a Model of Strengthening Morale Through Integrated Religious Education. Holding Inspiration Class activities in the form of sharing sessions by presenting successful practitioners and local youth so that the Village community remains enthusiastic about carrying out knowledge and religion. Storytelling Training for Parents as a form of re-socializing Fairy Tales as a means of character and religious education. Digital marketing training to increase the entrepreneurial capacity of the Sembungjambu Village community, and create working groups as follow-up activities. Evaluation and control of the process of implementing empowerment activities. It is hoped that this program can also be implemented in other villages in the context of strengthening morale. Desa Sembungjambu menyimpan potensi lokal yang perlu dikembangkan diantaranya tradisi masyarakat yang masih dijalankan dan terdapat dua makam wali Mbah Kyai Gede Ceper dan makam wali Mbah Datuk. Kendati demikian Desa Sembungjambu mempunyai problem sosial salah satunya kemerosotan moral yang ditandai dengan pergaulan bebas, alkoholisme dan komunitas yang dianggap deviant atau menyimpang dari norma masyarakat setempat. Salah satu upaya untuk menanggulangi degradasi moral ialah melalui pendidikan agama. Kegiatan pemberdayaan masyarakat ini menggunakan metode Participatory Rural Appraisal (PRA) model pemberdayaan partisipatif yang dilaksanakan di desa. Kegiatan ini dilakukan dengan tiga tahap yaitu Pertama perencanaan, Kedua, pelaksanaan dan Ketiga evaluasi. Kegiatan pemberdayaan ini diantaranya mengorganisir tokoh masyarakat Desa Sembungjambu dari semua elemen yang mempunyai keresahan atas isu kemerosotan moral, melakukan pemetaan potensi masyarakat yang bisa digunakan untuk proses Penguatan Moral melalui Focus Group Discussion, Melakukan pemetaan lembaga pendidikan formal, non formal dan informal di Desa Sembungjambu yang nantinya akan menghasilkan Model Penguatan Moral Melalui Pendidikan Agama Terinteragrasi. Mengadakan kegiatan Kelas Inspirasi berupa sharing session dengan menghadirkan praktisi dan local youth yang sukes agar masyarakat Desa tetap bersemangat mengemban ilmu pengetahuan dan agama. Pelatihan mendongeng untuk orang tua sebagai bentuk memasyarakatkan kembali Dongeng sebagai sarana pendidikan karakter dan agama. Pelatihan digital marketing dalam rangka peningkatan kapasitas wirausaha masyarakat, dan membuat kelompok kerja sebagai follow up kegiatan. Evalusi dan kontrol proses pelaksanaan kegiatan pemberdayaan. Harapannya program ini bisa juga dilaksanakan di desa lainnya dalam rangka penguatan moral.